A Study On The Extent Of Pond Accumulation Influence On Roadss Hydroplaning Phenomenon - Yunus, Nurul Yasarah Mohd (Universiti Sains Malaysia, 2017)
―Forgiving Road‖ is a designed and built road that prevents the causes of driving errors and reduces the consequences of driving errors. One problem encountered related to unforgiving road is the extent of pond accumulation influence hydroplaning which usually occurs on wet pavement. Hence, study about the extent of pond accumulation in Nibong Tebal, Pulau Pinang has been done. Two study locations in Nibong Tebal were selected. The extent of pond accumulation can be accessed through pond measurement test. Otherwise, the pavement quality in Nibong Tebal can be determined through the sand patch test and skid resistance test. All the results were analysed using SPSS Statistics Software in order to establish the relationship and correlation between the parameters. Moreover, it shows that both study locations had high risk of hydroplaning because the length of pond was more than 10m. The average texture depth for both sites was 0.07mm. The result of average skid resistance in study location 1 and 2 were 41 and 50 respectively. From the correlation analysis in study location 1, it shows only skid resistance correlate with length of pond. When length of pond increased, the skid resistance value decreased. Study location 2 shows no correlation between the related parameters. The extent of pond accumulation can be identified by determining the pavement quality and relationship of the parameter.